UPAYA MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI BERMAIN PLASTISIN - Khabibatur Rohmah, Siti; Gading, I Ketut (Universitas Pendidikan Ganesha, 2018)
This study aims to determine the improvement of children's fine motor skills through playing plasticine. This type of research is classroom action research (CAR) which is carried out in two cycles. The research subjects were 18 children in group A2 Semester I in Undiksha Singaraja Laboratory Kindergarten 2018/2019 Academic year. Data collection in this study was carried out by out by observation method with observation sheet instrument. The research data obtained were analyzed using descriptive statistical analysis techniques. The results showed that there was an increase in fine motor skills through playing plasticine. In the first cycle the achievement of fine motor skills was 57.62%, so it showed in the low category then it increased in the second cycle to 81.56% in the high category.Â Keywords : Play Plasticine, Fine Motor Skills